Status of Rhipicephalus microplus resistance to ivermectin, fipronil and fluazuron in Mato Grosso do Sul, Brazil - Valsoni, Luiza Mendes; Freitas, Mariana Green de; Borges, Dyego Gonçalves Lino; Borges, Fernando de Almeida (Revista brasileira de parasitologia veterinaria, 2021)
Abstract Southern cattle tick resistance to pour-on and injectable acaricides has yet to be evaluated on a broader scope, and the paucity of information on the subject may hinder efforts to control this parasite. The objective of this study was to evaluate the resistance profile of ten populations of Rhipicephalus microplus to the acaricides fluazuron, fipronil and ivermectin in cattle herds in Mato Grosso do Sul, Brazil. The larval immersion test (LIT) was used to evaluate susceptibility to ivermectin and fipronil and the adult immersion test (AIT) was performed to evaluate fluazuron. Samples were randomly obtained in ten farms, and in general, we found resistance in five samples to fluazuron and in four samples to ivermectin and fipronil. Six samples showed incipient resistance to ivermectin and fipronil. Five of the ten evaluated samples showed resistance and/or incipient resistance to all the active ingredients, and the other five to two active ingredients. Among the samples classified as resistant, the average resistance ratio for ivermectin was 2.75 and 3.26 for fipronil. These results demonstrate the advanced status of resistance to the most modern chemical groups for the control of R. microplus in the state of Mato Grosso do Sul. Resumo A resistência do carrapato-do-boi a acaricidas com modo de aplicação "pour-on" e injetáveis é pouco avaliada em estudos mais abrangentes, e essa escassez de informação pode resultar falhas no seu controle. Este estudo teve como objetivo avaliar o perfil de resistência em dez populações de Rhipicephalus microplus aos acaricidas fluazuron, fipronil e ivermectina, em rebanhos bovinos em Mato Grosso do Sul, Brasil. A caracterização fenotípica da resistência foi realizada por meio do teste de imersão de adultos (AIT) para o fluazuron, e teste de imersão de larvas (LIT) para fipronil e ivermectina. As amostras foram obtidas aleatoriamente em dez fazendas, sendo diagnosticada resistência em cinco amostras ao fluazuron e em quatro amostras à ivermectina e fipronil. Seis amostras apresentaram resistência incipiente à ivermectina e fipronil. Cinco das dez amostras avaliadas apresentaram resistência e / ou resistência incipiente a todos os princípios ativos, e as outras cinco a dois princípios ativos. Entre as amostras classificadas como resistentes, a média do fator de resistência para ivermectina foi de 2,75 e de 3,26 para fipronil. Esses resultados demonstram o avançado estado de resistência aos mais modernos grupos químicos para o controle de R. microplus em Mato Grosso do Sul.